Forest cover change analysis as a proxy: sustainability assessment using remote sensing and GIS in West Kalimantan, Indonesia - Dennis, R.A.; Colfer, C.J.P.; Puntodewo, A. (Resources for the Future and Center for International Forestry Research, 2001)
This study used a time series of remote sensing data from 1973, 1990 and 1994 to assess sustainability of forest use in three villages in West Kalimantan, Indonesia. This time period is characterised by a shift among three separate, recognised management systems: indigenous management; timber concessionaire management; and management as a wildlife reserve. Comparing remotely sensed data from three different sources with different spatial and spectral resolutions presented a technical challenge. A combined digital and visual classification methodology was adopted to produce comparable forest cover maps. These maps were combined within a geographical information system (GIS) with socioeconomic and cultural data. Quantitative change analysis over such a long period provided a valuable insight into forest cover dynamics in this area. The three villages selected for the study are characterised by two distinct patterns of resource use: shifting cultivation and capture fishery. Comparison of the forest change maps over the 21-year period shows that forest loss among the community of shifting cultivators is 7% less than forest loss for one of the fishing communities. Remarkably, the other fishing community examined shows only a 1.5% loss in forest over the 21-year period. Through this work we have combined forest cover change with ethnographic and socioeconomic data (both in a GIS and by conventional means). We feel that this approach can make a valuable contribution to assessing sustainability.